Harm and Harmony—Concepts of Nature and Environmental Practice in Japan - Regina M. Bichler (Histories, 2023)
Japan is often surrounded by the myth of featuring a unique “love for nature”, and its traditional culture and lifestyle as having been “in harmony with nature” before it was corrupted by modernization and Westernization. In this paper, I employ three examples to delineate images of nature in different times of Japanese history and point out the discrepancy between discourse on nature and physical engagement with nature. I argue that the environmental destruction that peaked in the Meiji period (1868–1912) is not primarily derived from a new, dualistic Euro-American understanding of nature. Rather, I demonstrate that environmental harm was already inherent in premodern Japan and was reconcilable with the respective concepts of nature. Therefore, industrialization and the adoption of Western technology solely released the potential for large-scale environmental impact.